Lapin ihminen Identifikaatiot, ympäristöt ja yhteinen erityisyys - Nykänen, Tapio (Tietolipas, 2022)
Finnish Lapland is a historical borderland of Finnish and Sámi cultures. Such a region offers various social-political identifications for people to choose: people may see it possible to identify as Finnish, Laplanders, Lappish or Sámi, for instance. However, the choices have social and political limits, and some identifications are more contested than others. The book examines the processes of identifications in the middle parts of Lapland, just south of the region defined as Sámi homeland in Finland. While the study reveals differences and nuances in people's thinking, it also shows that there is a recognizable sense of shared cultural specifity around the region. Lapland is conceptualized as an extraordinary place with unusual nature and history, characterized by particular livelihoods (such as reindeer herding) and lively cultural interaction. The book concludes that while Lapland is extraordinary as a historical dwelling region of indigenous Sámi, it may be politically significant to recognize it as a unique borderland of cultures with features of its own.